2012
DOI: 10.1016/j.jacc.2012.06.036
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Exercise Training in Chronic Heart Failure

Abstract: Moderate supervised ET performed twice weekly for 10 years maintains functional capacity of more than 60% of maximum Vo(2) and confers a sustained improvement in quality of life compared with NT patients. These sustained improvements are associated with reduction in major cardiovascular events, including hospitalizations for CHF and cardiac mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
197
1
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(234 citation statements)
references
References 24 publications
10
197
1
21
Order By: Relevance
“…Regarding year of publication, nine articles were dated 2012 (15)(16)18,(20)(21)(22)(29)(30)(31) , followed by years 2011 (n=6) (11)(12)(13)17,19,23,33) , 2010 (n=4) de la salud que tratan de personas con insuficiencia cardiaca. Futuras revisiones sistemáticas con meta-análisis son necesarias para identificar las intervenciones más eficaces para mejorar la calidad de vida de estos individuos.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Regarding year of publication, nine articles were dated 2012 (15)(16)18,(20)(21)(22)(29)(30)(31) , followed by years 2011 (n=6) (11)(12)(13)17,19,23,33) , 2010 (n=4) de la salud que tratan de personas con insuficiencia cardiaca. Futuras revisiones sistemáticas con meta-análisis son necesarias para identificar las intervenciones más eficaces para mejorar la calidad de vida de estos individuos.…”
Section: Resultsunclassified
“…Regarding year of publication, nine articles were dated 2012 (15)(16)18,(20)(21)(22)(29)(30)(31) , followed by years 2011 (n=6) (11)(12)(13)17,19,23,33) , 2010 (n=4) (24)(25)32,34) , 2013 (n=3) (14,(27)(28) and 2008 (n=1) (26) . The articles were published in General Cardiology journals (12)(13)(16)(17)(18)20,22,(24)(25)(28)(29)(30)(31)(32)34) , followed by General Clinical journals (14)(15)(26)(27)33) . Two articles were published in Nursing journals (19,23) and one was published in a Nutrition journal (21) (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the results for quality of life were not different between the groups, it can be observed that in the present study day-to-day activities, represented by the 6MWT, CT and ST, were impaired for patients with HF+PVI. We believe that histological abnormalities in skeletal muscle of HF patients, such as muscle atrophy and reduced mitochondrial density, [21][22][23] may have impacted these patients' capacity for microvascular O 2 extraction. This in turn suggests that the patients with mixed disease suffer greater musculoskeletal compromise, leading to lower tolerance of exercise, as observed in the clinical tests.…”
Section: Discussionmentioning
confidence: 98%